Principal Trends, Problems and Prospects of Development of Linguistic Personology (Linguostylistic Studies, 2015)
The article deals with topical problems of linguistic personology as a new branch of linguistics. They include an identification of language personality as an object of research, ascertainment of the nature of this basic concept, development of general principles and methods, uniform technique of analysis and description of language personality. Based on the analysis of well-known publications, the principal areas of researches in linguistic personology are described, as well as an attempt to predict the dynamics of development of this scientific discipline is made. Language personality is studied in linguodidactic, linguoculturological, linguopoetic, sociolinguistic and psycholinguistic areas. Description of idiolectic language personalities and their ethnocultural or social types seems productive. Integrative study of language personality will contribute to formation of theory and methodology of linguistic personology and strengthening of its status as an independent science. Key words: linguistic personology, language personality, model of language personality. References